Penentuan Lima Objek Wisata Terfavorit di DKI Jakarta Menggunakan SAW dan WP Berbasis Web - Susanto, Arman Rama; Wahyuddin, M Iwan; Andrianingsih, Andrianingsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The purpose of this research is to create a web-based tourist attraction information system in the DKI Jakarta area. The benefit of this research is to find out information on tourist attractions such as addresses, routes and tourist attractions that you want to go to through a web-based system that has been created. In the research method that researchers use in system design consists of Unified Modeling Language (UML), Use Case Diagrams, Class Diagrams, Implementation. While the development method using Simple Additive Weighting (SAW) and Weight product (WP) method. Based on the process and research, it can be concluded that the Simple Addictive Weight (SAW) algorithm gives more accurate results than the Weight product (WP) algorithm. So that the user can make a selection of the tourist attraction to be visited after seeing the list of tours available on the Enjoy Jakarta website. Then give an assessment of the tourist attractions that have been visited.